A New Hybrid Vertical Coordinate Ocean Model and Its Application in the Simulation of the Changjiang Diluted Water - 张文静 朱首贤 董礼先 张长宽 (China ocean engineering, 2011)
Based on the analysis of the advantages and disadvantages of some vertical coordinates applied in the calculation of the Changjiang diluted water （CDW）, a new hybrid vertical coordinate is designed, which uses σ coordinate for current and σ-z coordinate for salinity. To combine the current and salinity, the Eulerian-Lagrangian method is used for the salinity calculation, and the baroclinic pressure gradient （BPG） is calculated on the salinity sited layers. The new hybrid vertical coordinate is introduced to the widely used model of POM （Princeton Ocean Model） to make a new model of POM-σ-z. The BPG calculations of an ideal case show that POM-σ-z model brings smaller error than POM model does. The simulations of CDW also show that POM-σ-z model is better than POM model on simulating the salinity and its front.